Cover Picture: Redox‐Switchable Ring‐Closing Metathesis: Catalyst Design, Synthesis, and Study (Chem. Eur. J. 33/2013). Issue 33 (2nd August 2013) - Arumugam, Kuppuswamy; Varnado, C. Daniel; Sproules, Stephen; Lynch, Vincent M.; Bielawski, Christopher W.
<x xml:space="preserve">Abstract</x> Jolting electrons out of catalysts bearing redox‐active ferrocene groups reduces their activities in ring‐closing metathesis reactions; subsequent reduction restores catalytic performance. For more details see the Full Paper by C. W. Bielawski et al. on page 10866. The authors are indebted to Dr. Angel Syrett for her kind assistance with the graphics.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>